2020
DOI: 10.3389/fmed.2020.00045
|View full text |Cite
|
Sign up to set email alerts
|

Fostering the Resilience of People With Dementia: A Narrative Literature Review

Abstract: Background: Resilience is a process through which people use resources to adapt to adversity. Interventions aiming to support resilience in people with dementia have been developed. However, the optimal content, structure and impact of these interventions is unclear. This literature review explores the factors through which interventions foster resilience in people with dementia and examines their efficacy. Methods: Eight databases were searched systematically, for literature published from 2000 to 2019. Follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 63 publications
0
11
0
2
Order By: Relevance
“…This is in line with the recommendations of a realist review by Li, Keady and Ward [ 144 ] who state that that the dynamic relationship between people living with dementia and their everyday neighbourhood have impact on their health and especially social health. An everyday lens implies that in order to foster the resilience of people living with dementia there needs to be an additional focus on neighbourhood and asset-based community interventions alongside individual support [ 145 ], in order to promote social inclusion, as stated by the Global Action Against Dementia of the World Health Organization [ 146 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with the recommendations of a realist review by Li, Keady and Ward [ 144 ] who state that that the dynamic relationship between people living with dementia and their everyday neighbourhood have impact on their health and especially social health. An everyday lens implies that in order to foster the resilience of people living with dementia there needs to be an additional focus on neighbourhood and asset-based community interventions alongside individual support [ 145 ], in order to promote social inclusion, as stated by the Global Action Against Dementia of the World Health Organization [ 146 ].…”
Section: Discussionmentioning
confidence: 99%
“…Auch werden Menschen mit Demenz von der so wichtigen Ressource für Resilienz – nämlich den sozialen Kontakten und der zwischenmenschlichen Interaktion – abgeschnitten. In vielen bisherigen Studien zu Resilienz bei Menschen mit Demenz wurde gerade der Faktor von sozialer Unterstützung und sozialer Interaktion als wesentlich und wichtig beschrieben [ 30 ]. Im Rahmen der Demenz nehmen auch Möglichkeiten zur Nutzung und Entwicklung von Coping-Strategien ab.…”
Section: Ergebnisse Und Problemfelderunclassified
“…Resilience-centered interventions can be seen as one important approach to adapting to stress and reducing the adverse impact of the stressors ( 7 ). Luthar and Cicchetti ( 14 ) defined resilience as “a dynamic and amendable process,” in which people use resources to acclimate to adversity ( 15 ). Meanwhile, Kunzler et al ( 16 ) highlighted that resilience-centered interventions could be seen as the process of maintenance, withstanding, overcoming, adjustment, adaptation, posttraumatic growth, stress-related growth, rebound from a stressor, or rapid readjustment.…”
Section: Introductionmentioning
confidence: 99%
“…Windle et al ( 30 ) studied tools for resilience interventions and concluded that the conceptual and theoretical adequacy of the scales was questionable, with no existing “gold standard” of resilience measures. Whelan et al ( 15 ) indicated that key sets of outcomes for resilience in neurocognitive disorders have not been identified. For example, Ghanei Gheshlagh et al ( 7 ) used three scales, which are Resilience Scale-25 (RS-25), Connor–Davidson Resilience Scale-10 (CDRISC-10), and Connor–Davidson Resilience Scale-25 (CDRISC-25), to assess the effectiveness of the resilience process for people with chronic physical diseases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation